2016
DOI: 10.1371/journal.pone.0154451
|View full text |Cite
|
Sign up to set email alerts
|

Low Insulin-Like Growth Factor-1 Level in Obesity Nephropathy: A New Risk Factor?

Abstract: IntroductionIGF-1 (insulin-like growth factor-1) is a hormone involved in cell growth and other important processes. In the kidney, IGF-1 has a stimulating effect, increasing the blood flow and glomerular filtration rate. Although many experimental animal studies regarding the role of IGF-1 in the kidney have been conducted, few human studies are available in the literature. Obesity is a cause of renal failure, and several glomerular lesions associated with obesity have been described. However, no studies rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In addition to Nrf2, previous studies also provide evidence that insulin-like growth factor-1 (IGF-1)-mediated pathways exert multifaceted cerebromicrovascular protective effects, which act to preserve endothelial vasodilation and NVC (47, 76, 99-104). Aging results in decreased levels of circulating IGF-1 (102,(105)(106)(107). Mouse models of genetic IGF-1 deficiency were shown to exhibit accelerated neurovascular aging phenotype, characterized by neurovascular uncoupling, impaired endothelial NO production, and cognitive impairment (76).…”
Section: Endothelial Dysfunction and Neurovascular Uncouplingmentioning
confidence: 99%
“…In addition to Nrf2, previous studies also provide evidence that insulin-like growth factor-1 (IGF-1)-mediated pathways exert multifaceted cerebromicrovascular protective effects, which act to preserve endothelial vasodilation and NVC (47, 76, 99-104). Aging results in decreased levels of circulating IGF-1 (102,(105)(106)(107). Mouse models of genetic IGF-1 deficiency were shown to exhibit accelerated neurovascular aging phenotype, characterized by neurovascular uncoupling, impaired endothelial NO production, and cognitive impairment (76).…”
Section: Endothelial Dysfunction and Neurovascular Uncouplingmentioning
confidence: 99%
“…Despite various attempts to elucidate the pathogenic mechanisms of renal disease in obesity, most of which have been experimental, there is still a lack of knowledge on this subject, and further investigation is needed. Only a few studies have reported associations among obesity, renal injury and inflammatory hormones [5153]. Insulin-like growth hormone-1 (IGF-1) levels are decreased in obesity [54, 55].…”
Section: Obesity As a State Of Chronic Inflammationmentioning
confidence: 99%
“…Insulin-like growth hormone-1 (IGF-1) levels are decreased in obesity [54, 55]. We have recently identified a link between a low IGF-1 hormone level and the presence of renal injury in MO patients with early stages of ORG [53]. Additionally, IGF-1 gene expression has been shown to be decreased in kidney biopsies from MO patients with early stages of ORG compared with those from a normal-weight control group (M. Navarro, unpublished data), whereas expression of the proinflammatory genes IL-6 and glucose transporter-1 was increased (M. Navarro, unpublished data).…”
Section: Obesity As a State Of Chronic Inflammationmentioning
confidence: 99%
“…Consistently, our current study shows that IGF-1 levels are significantly lower in obesity group compared to healthy controls. In a study conducted with morbidly obese individuals, it has been reported that decreased serum IGF-1 levels are related with renal lesions [20].…”
Section: T a B L E 1 Demographic And Clinical Features And Biochemical Parameters Of Healthy And Obese Participantsmentioning
confidence: 99%